Influences of sedimentation on overflow properties of sharp-crested weir - Mohammad Mehdi Farzanmehr; Jahanshir Mohammadzadeh-Habili (International Journal of Sediment Research)
A sharp-crested weir is the simplest type of weir and is mainly used for discharge measurement in open channels. The surface profile of an ogee weir also is designed based on the lower nappe profile of the free jet passing over a sharp-crested weir. In the current study, influences of sedimentation on the discharge coefficient and lower nappe profile of a sharp-crested weir were experimentally investigated. The results indicated that for a specific discharge value, an increase in upstream sedimentation depth results in the reduction in the water level of the approach flow to the sharp-crested weir, and, consequently, a reduction in the weir water head. As the discharge coefficient is inversely influenced by the weir water head, increases in the sedimentation depth resulted in raising the discharge coefficient of the sharp-crested weir up to 42%. Furthermore, the results indicated that with increases in upstream sedimentation depth, the lower nappe profile of the free jet passing over the sharp-crested weir tends toward that of a vertical drop. Under upstream sedimentation, the discharge coefficient of the sharp-crested weir is mainly influenced by the weir's effective height (difference between weir height and sedimentation depth) and it is minimally influenced by sediment grain sizes. Using the experimental results supported by dimensional analysis, the discharge coefficient of the sharp-crested weir was accurately derived as an increasing function of the ratio of weir water head to weir effective height.